RETRACTED: Mitochondrial dysfunction and cell death induced by Toona sinensis leaf extracts through MEK/ERK signaling in glioblastoma cells - Yu-Feng Su; Tai-Hsin Tsai; Keng-Liang Kuo; Chieh-Hsin Wu; Hui-Yuan Su; Wen-Chang Chang; Fu-Long Huang; Ann-Shung Lieu; Aij-Lie Kwan; Joon-Khim Loh; Chih-Lung Lin; Cheng Yu Tsai (PLoS ONE, 2025)
Toona sinensis, a kind of phytochemicals in traditional Chinese medicine widely used in South-East Asia, has been recognized for its anticancer properties, particularly against various types of cancer. We aimed to evaluate the effectiveness of T. sinensis leaf extracts (TSL) specifically for glioblastoma multiforme (GBM). Gallic acid was identified as the major active component in the aqueous extracts of TSL using the HPLC system. Furthermore, it has been shown to have the ability to penetrate the blood-brain barrier. Various concentrations of TSL (10, 20, 40, and 80 μg/mL) were applied and 80 μg/mL TSL treatment significantly inhibited cell growth, proliferation, and cytotoxicity in A172 and U251 GBM cells. Flow cytometry analysis revealed cell cycle arrest at the G2/M phase and increased apoptotic cells. Furthermore, we observed mitochondrial dysfunction characterized by elevated ROS levels and reduced ATP production due to the blockade of electron transport chain (ETC) complexes. TSL treatment regulated this ROS-induced mitochondrial dysfunction. Western blotting analysis showed upregulation of Bax and Puma, along with downregulation of Bcl-2. Additionally, TSL treatment induced the cleavage of caspase-3, caspase-9, and PARP, indicating activation of the mitochondria-mediated apoptosis pathway and caspase-dependent pathway in both GBM cell lines. To investigate the involvement of the MEK/ERK pathway in TSL-induced effects, we used U0126, an inhibitor of MEK/ERK kinase. The results demonstrated that TSL treatment suppressed MEK/ERK activation, inhibiting ROS-induced mitochondrial dysfunction and promoting apoptosis. This suggests a potential therapeutic strategy targeting the MEK/ERK pathway in GBM treatment. Overall, our findings indicate that TSL treatment exerts cytotoxic effects through ROS-mediated mitochondrial dysfunction and activation of apoptotic pathways via MEK/ERK pathway in GBM cells. These insights provide valuable knowledge for potential therapeutic applications of TSL in GBM treatment.